Facile Synthesis of 4-Arylidene-1H-imidazol-5(4H)-ones by an Ugi–Aza-Wittig Sequence - Wang, Ying; Xie, Hai; Pan, Yu-Rong; Ding, Ming-Wu (Synthesis, 2014)
Vinyl azides, obtained from the Ugi-type reaction of 2-azido-3-arylacrylic acid, secondary amine, aldehyde, and isocyanide, react with triphenylphosphine to give a variety of 4-arylidene-1H-imidazol-5(4H)-ones in high yields via sequential Staudinger and intramolecular aza-Wittig reaction.
Keywords: 1H-imidazol-5(4H)-ones; Ugi reaction; aza-Wittig reaction; iminophosphoranes; azides